Errata in CPUs and how designers can manage them better - Galvan, Glenn (Knovel, 2011)
A cell phone crashes or a Notebook laptop ceases to function. There are countless reasons why these unwanted events happen. It could stem from human body electrostatic discharge (ESD), software operating issues, an incompatible application loaded into the platform, memory errors heat or even errata in the main Central Processor Unit (CPU). This article will focus on errata in CPUs and how computer designers and other corporate personnel, such as project managers, can better manage CPUs through knowledge and tools for a specific products life cycle. --